Adult firefly abundance is linked to weather during the larval stage in the previous year. (28th November 2018) - Evans, Tracy R.; Salvatore, Donald; van de Pol, Martijn; Musters, C.J.M.
Abstract : 1. Much is known about the brief adult phase of fireflies. However, fireflies spend a relatively long developmental period under the soil surface. Climatic and soil conditions may directly affect the eggs, larvae, and pupae, and also affect them indirectly through predators, competitors, and prey items. Climatic conditions during the early life stages of this iconic species are therefore relevant to their hypothesised decline within the context of global warming. 2. Data on the abundance of fireflies were extracted from the publicly available citizen dataset across North America over a period of 9 years. The effects of weather in the 24 months before the observations of firefly abundance were documented based on 6761 observations. 3. Climatic conditions during both the larval and adult phases have a non‐linear effect on adult firefly abundance. Maximum winter and spring temperatures and mean precipitation in the 20‐month period before the observations had the greatest impact on the abundance of firefly adults. Low maximum soil moisture during the 5–19 months preceding the observations affected the adult abundance negatively, and high maximum soil moisture affected it positively. 4. After correcting the firefly abundance for these weather effects, it is estimated that the abundance of fireflies increased over the time period of this study. 5. This study suggests that early life climatic conditions have a small but significant impact on adult firefly abundance with a total R 2 of 0.017. Abstract : This study suggests that larval climatic conditions have a small but significant impact on adult firefly abundance in the United States. Impacts of temperature begin 6 months before peak flashing behaviour is observed. There are optimal amounts of precipitation and soil moisture; more or less than these values are associated with lower abundance.